How did the Impact of the 2nd Wave of COVID-19 on Parking Characteristics at Non-Referral Hospitals? Case Study: Permata Cibubur Hospital, Indonesia - Andri Irfan Rifai; Roisman A. Harefa; Muhammad Isradi; Amar Mufhidin (NAROTAMA UNIVERSITY, Indonesia, 2021)
The health industry is vital in this modern era, including providing hospital facilities in various places. However, the Corona Virus Disease (COVID-19) pandemic has changed people's habits in using health services. Community visits to hospitals changed when the first wave of COVID-19 occurred in March 2021 and the second wave in June 2021. Parking facilities as part of hospital services are part of the affected by this pandemic condition. The purpose of this paper is to determine changes in parking demand in the before, first wave, and second-wave phases of COVID-19. The research method is carried out by conducting surveys and calculating parking characteristics. The analysis shows that parking demand decreased during the first wave and then increased again during the second wave. The first-wave parking index decreased by 44.90% compared to before the pandemic and increased by 112.24% during the second wave.